2009
DOI: 10.1103/physrevb.80.155451
|View full text |Cite
|
Sign up to set email alerts
|

Very low thermally induced tip expansion by vacuum ultraviolet irradiation in a scanning tunneling microscope junction

Abstract: The thermal and photoelectronic processes induced when a vacuum ultraviolet ͑VUV͒ laser irradiates the junction of a scanning tunneling microscope ͑STM͒ are studied. This is performed by synchronizing the VUV laser shots with the STM scan signal. Compared to other wavelengths, the photoinduced thermal STM-tip expansion is not observed when the VUV radiation is freed from spurious emissions. Furthermore, we demonstrate that the purified VUV photoinduced transient signal detected in the tunnel current is entirel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The issue of the photothermal STM tip expansion is thus crucial for these experiments. We have shown that in our experimental conditions (i.e., low temperature, short wavelength, low focusing), STM tip expansion can be extremely weak and thus negligible, contrary to other experiments, 14,15 if the laser repetition rate does not exceed 20 Hz 16,17 (see Supporting Information). The laser irradiation is combined with a surface voltage pulse, i.e., the controlled variation of the silicon surface voltage.…”
mentioning
confidence: 56%
“…The issue of the photothermal STM tip expansion is thus crucial for these experiments. We have shown that in our experimental conditions (i.e., low temperature, short wavelength, low focusing), STM tip expansion can be extremely weak and thus negligible, contrary to other experiments, 14,15 if the laser repetition rate does not exceed 20 Hz 16,17 (see Supporting Information). The laser irradiation is combined with a surface voltage pulse, i.e., the controlled variation of the silicon surface voltage.…”
mentioning
confidence: 56%
“…Yet, internal molecular dynamics is still reserved for photoinduced surface processes as barely ultrafast laser interaction pump-probe experiment can fit nicely within the internal quantum evolution of excited molecular structures [22,23]. However, experiments that tend to mix pulsed laser with a local probe microscope still need a deep understanding of the photo-induced processes in the STM junction [24,25]. In this context, we have investigated the irradiation of the STM junction with a pulsed excimer laser at 157 nm when the surface of a Si(100):H is imaged (figure 5(a)).…”
Section: Resolving the Tunnel Current Dynamics Of Photo-induced Proce...mentioning
confidence: 99%
“…The experiments are carried out with two types of wavelengths: an IR photo-excitation, which results from the separation of the spurious emission in the laser cavity, and a pure VUV irradiation. To resolve the STM junction dynamics behaviour, we have triggered both laser irradiation wavelengths with the scanning movement of the STM tip so that a single laser shot is applied during a lateral STM tip scan [25]. Hence, during the STM topography combined with laser irradiation, both feedback signal and tunnel current can be analysed.…”
Section: Resolving the Tunnel Current Dynamics Of Photo-induced Proce...mentioning
confidence: 99%
“…This can lead to unwanted signals [106] and localized damage to the surface under the tip resulting from field enhancement in the tunnel junction [107]. However, recent proof of principle work by Riedel et al [108] has shown that under certain circumstances it is possible to decouple radiation induced electron and thermal excitation allowing, in this case, a photoelectron signal to measured.…”
Section: Ultrafast Scanning Tunnelling Microscopymentioning
confidence: 99%